Is There an Enabling Environment for Nutrition-Sensitive Agriculture in East Africa?: Stakeholder Perspectives From Ethiopia, Kenya, and Uganda. (December 2015) - Hodge, Judith; Herforth, Anna; Gillespie, Stuart; Beyero, Mesfin; Wagah, Margaret; Semakula, Richard
Background: There is growing recognition that "nutrition-sensitive" development is necessary to ensure nutrition security and reduce malnutrition. While agriculture has the potential to be a strong driver of malnutrition reduction and serves as the main source of livelihood for approximately two-thirds of East Africa's population, its potential to reduce malnutrition is currently not being realized. Objective: Leveraging Agriculture for Nutrition in East Africa is a research study based in Ethiopia, Kenya, and Uganda that seeks to understand the enabling environment necessary for optimizing the contribution of the food and agriculture sector to nutrition outcomes. Its objectives were to explore stakeholder perceptions of nutrition–agriculture linkages, of political and institutional challenges and opportunities, of evidence that is available and influential for policy making, and of key issues with regard to capacity. Methods: Open-ended and semistructured interviews were conducted with 53 stakeholders from government, civil society, donors, United Nations organizations, private sector, and research/academic institutions in Ethiopia, Kenya, and Uganda in 2014. Results: Although policy opportunities and contexts are different between the 3 countries, stakeholders identified similar barriers to greater action, including a narrow focus on solely market-oriented and staple crop production, a lack of clarity and incentives within the agriculture sector about improving nutrition and how to translate policy into action, and lack of capacity in human and financial resources. Many actions to improve the nutrition sensitivity of agriculture were mentioned, including crop diversification, value chain activities and improved market access, nutrition education, and reduction in time and labor costs to women. Conclusion: Many opportunities exist to strengthen the impact of agriculture on nutrition in East Africa, but stronger formulation and implementation of policies will require adequate human resources, funds, timely data on the context, sector alignment on priority actions, and alignment on a framework or indicators for accountability.